2021
DOI: 10.1186/s12903-021-01914-4
|View full text |Cite
|
Sign up to set email alerts
|

Nattokinase crude extract enhances oral mucositis healing

Abstract: Background Nattokinase (NK) is a promising alternative in the prevention and treatment of cardiovascular diseases due to its potent fibrinolytic activity. In this study, we investigated the effect of crude nattokinase extract on the healing of acetic acid-induced oral mucositis in mice. Methods Bacillus subtilis culture media (BSCM) was isolated into the supernatant, named nattokinase crude extract (NCE), and the pellet was named Bacillus subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This phenomenon may be attributed to the development of oral mucositis and inflammation induced by the application of acetic acid, resulting in pain and discomfort while eating and swallowing. 43,44 Then, on days 3 and 4, the food intake of mice in groups L and H gradually recovered following LTE application, while group M only demonstrated a slight increase (Fig. 2c).…”
Section: Food and Function Papermentioning
confidence: 91%
“…This phenomenon may be attributed to the development of oral mucositis and inflammation induced by the application of acetic acid, resulting in pain and discomfort while eating and swallowing. 43,44 Then, on days 3 and 4, the food intake of mice in groups L and H gradually recovered following LTE application, while group M only demonstrated a slight increase (Fig. 2c).…”
Section: Food and Function Papermentioning
confidence: 91%
“…134 It has also been found that NK inhibits the restenosis of rabbit abdominal arteries after percutaneous transluminal angioplasty and exhibits significant potential to reduce pain and promote healing of oral mucositis. 135,136 Furthermore, ascites and tumor growth were significantly reduced and the survival rate increased to 31% after feeding NK crude extract to mice with liver cancer (Fig. 4).…”
Section: Antioxidationmentioning
confidence: 95%
“…In addition to the research of nattokinase in the fields of thrombosis and hypertension treatment, nattokinase can also be used as a drug or adjuvant to treat diseases such as cancer [ 11 ], Alzheimer’s disease (AD) [ 104 ], retinopathy [ 10 ], hyperlipidemia [ 105 ] and oral mucositis [ 106 ]. Nattokinase has broad prospects in the field of cancer treatment and is expected to become an effective means of cancer treatment in the future.…”
Section: Clinical Application Of Nattokinasementioning
confidence: 99%